Analyzing semantic shifts in English and German by exploring historical influences and societal dynamics - Asri, Wahyu Kurniati; Rhamadanty, Winda Ayu Utami; Burhamzah, Muftihaturrahmah; Alamsyah, Alamsyah (Universitas Syiah Kuala, 2024)
This research examines the mechanisms of semantic change in English and German, focusing on comparing and contrasting these processes across the two languages and investigating the influence of major historical events and societal shifts. By utilizing digital text corpora, libraries, archives, and modern digital media, the study conducts qualitative analyses, including case studies and discourse analysis, to explore semantic evolution. Thematic analysis was employed to thoroughly examine and interpret the data, allowing for the identification of recurring patterns, themes, and significant insights. The results showed that both English and German undergo significant semantic shifts driven by a metaphorical extension (i.e., narrowing or broadening of meanings, pejoration and amelioration, frequency and pathway of change, cultural and historical influences) and historical events and societal shifts that influence semantic change (i.e., wars and conflicts, industrialization, technological advancement, globalization, and cultural exchange, societal movements, and ideological shifts). The role of metaphorical extension is seen in adapting language to technological advancements while highlighting linguistic evolution through narrowing and broadening meanings influenced by cultural, historical, and linguistic factors. Additionally, pejoration and amelioration reflect societal changes and attitudes. Historical events and societal shifts, such as wars, industrialization, technological advancements, globalization, and social movements, significantly impact semantic changes in both English and German. These external influences catalyze language use and meaning shifts, illustrating the interaction between language and human experience.